The clinical presentation and outcome of tuberculosis in children admitted to a paediatric intensive care unit in an area with a high incidence of pulmonary tuberculosis - Heyns, Louis (Department of Paediatrics and Child Health, 2017)
The purpose of this study was to measure and evaluate the clinical presentation, outcome and longterm effects of tuberculosis in children admitted to the paediatric intensive care unit at Tygerberg Hospital. A retrospective, descriptive study was conducted among 57 children admitted to the paediatric intensive care unit between January 1991 to December 1994. The sample comprised all the children with tuberculosis aged one month to twelve years who were admitted to the paediatric intensive care unit. Audit measures were taken to ensure that all the children with tuberculosis were identified. Data was collected by means of a structured working sheet and questionnaire that was sent to the clinics. Respondents completed the questionnaire in the clinics. There was an increase in the incidence of children suffering from pulmonary or disseminated tuberculosis who required admission to the PICU, although the incidence of HIV was low. None of the index cases had MDR-TB. Fifty-one percent of children were admitted to the PICU because of primary tuberculosis or complications of the disease. Of these children 69 % had respiratory failure who required ventilation. Thirty percent were admitted to the PICU for respiratory failure and were subsequently diagnosed as having tuberculosis. Tuberculosis was incidently found amongst 4 children when they were routinely examined in the PICU. Due to the difficulty in confirming the diagnosis of tuberculosis in children, a large proportion of cases go unrecognised. The chest radiographs demonstrated that hilar ( 40 % ) and paratracheal (32 % ) adenopathy was the most common findings. Bronchial compressions was present in 12 % of cases. A significantly positive Mantoux skin test was reported in 35 % of cases and 53 % had a positive Tine skin test. Gastric aspirates positive for M. tuberculosis were obtained in 42 % of cases and of cultures other than gastric aspirates, 44 % were positive. Other special investigations to confirm the diagnosis of tuberculosis included CT scan and bronchoscopies. Bronchoscopies were performed on 13 children and found to be abnormal in 12 cases. The most common finding was nodal compression of the airways. Overall the diagnosis of confirmed tuberculosis was made in 47% and of probable tuberculosis in 53 % of cases. The length of stay in the PICU was 10.2 + 22.4 days. The PICU mortality was 23%, with a total hospital mortality of 26%. The mortality for the TBM subgroup was 75 % . Although a good compliance (82 % ) was recorded by the clinics in the follow-up study, they experienced problems with the notifications. The follow-up study pointed out that communication was a problem between the referring hospital and the clinics. Thirty-one percent of the clinics made suggestions for improving the communication. The findings demonstrates that in an area with a high incidence of TB, children do develop severe disease requiring admission to the PICU. This places a considerable clinical and financial burden on the already limited health system. Early diagnosis of TB should prevent severe disease and subsequent admission to the PICU. The increasing incidence of HIV and MDR-TB will undoubtedly pose a major risk to ICU staff and the prevention of infection is of primary concern for those who may be exposed in this area. Due to this, certain recommendations regarding guidelines for admission to the PICU, investigations of patients exposed of having TB in the PICU, prevention of infection and detection of disease in staff in the PICU, the need for increase beds in the PICU and recommendations post discharge from the PICU were made.